2018
DOI: 10.7762/cnr.2018.7.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Links between Serine Biosynthesis Pathway and Epigenetics in Cancer Metabolism

Abstract: Cancer metabolism is considered as one of major cancer hallmarks. It is important to understand cancer-specific metabolic changes and its impact on cancer biology to identify therapeutic potentials. Among cancer-specific metabolic changes, a role of serine metabolism has been discovered in various cancer types. Upregulation of serine synthesis pathway (SSP) supports cell proliferation and metastasis. The change of serine metabolism is, in part, mediated by epigenetic modifiers, such as Euchromatic histone-lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…NADPH and methyl groups are generated via folate and methionine metabolism. Consequently, in addition to amino acids, the serine biosynthesis process produces reducing potential and methyl groups that are involved in post-translational modification and epigenetic regulation [ 29 ]. PHGDH is genetically and transcriptionally upregulated in diverse cancer cell lines.…”
Section: Metabolic Characteristics Of Cancersmentioning
confidence: 99%
“…NADPH and methyl groups are generated via folate and methionine metabolism. Consequently, in addition to amino acids, the serine biosynthesis process produces reducing potential and methyl groups that are involved in post-translational modification and epigenetic regulation [ 29 ]. PHGDH is genetically and transcriptionally upregulated in diverse cancer cell lines.…”
Section: Metabolic Characteristics Of Cancersmentioning
confidence: 99%
“…Additionally, glycine can be converted to threonine. This pathway provides precursors for purine biosynthesis and the tricarboxylic acid (TCA) cycle [20]. The TCA cycle generates ATP for protein production.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal activity of the serine and glycine signaling pathways provides the main guarantee for satisfying the abundant nutrient requirements of tumor cells (34). In addition, the serine signaling pathway can provide biological precursors for many substances, such as proteins, nucleic acids, fatty acids, and cell membranes for tumor cell proliferation (35). Some studies have shown that abnormal methylation in tumor cells may affect the gene regulation process of this pathway (36).…”
Section: Discussionmentioning
confidence: 99%